2019
DOI: 10.1155/2019/7692973
|View full text |Cite|
|
Sign up to set email alerts
|

Preconditioning of Rat Bone Marrow-Derived Mesenchymal Stromal Cells with Toll-Like Receptor Agonists

Abstract: Bone marrow-derived mesenchymal stromal cells (BM-MSCs) are dynamic cells that can sense the environment, adapting their regulatory functions to different conditions. Accordingly, the therapeutic potential of BM-MSCs can be modulated by preconditioning strategies aimed at modifying their paracrine action. Although rat BM-MSCs (rBM-MSCs) have been widely tested in preclinical research, most preconditioning studies have employed human and mouse BM-MSCs. Herein, we investigated whether rBM-MSCs modify their pheno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 102 publications
0
6
0
Order By: Relevance
“…Further research revealed that MSC2 adopted an immune-suppressive phenotype by secreting anti-inflammatory soluble factors, including IDO, IL-10, PGE2, and TGF- β [ 24 ]. Conversely, MSC1 exhibited a phenotype characterized by high levels of CCL3, CCL4, CCL9, CCL10, IL-1 β , and TNF- α and low levels of IDO [ 25 ]. These findings suggest that the concept of MSCs polarization into an anti-inflammatory phenotype through distinct TLR agonists is an attractive strategy to enhance the anti-inflammatory capabilities of MSCs, and some studies have demonstrated poly(I:C)-pretreated MSCs exhibit strengthened effects in decreasing kidney ischemia/reperfusion injury [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Further research revealed that MSC2 adopted an immune-suppressive phenotype by secreting anti-inflammatory soluble factors, including IDO, IL-10, PGE2, and TGF- β [ 24 ]. Conversely, MSC1 exhibited a phenotype characterized by high levels of CCL3, CCL4, CCL9, CCL10, IL-1 β , and TNF- α and low levels of IDO [ 25 ]. These findings suggest that the concept of MSCs polarization into an anti-inflammatory phenotype through distinct TLR agonists is an attractive strategy to enhance the anti-inflammatory capabilities of MSCs, and some studies have demonstrated poly(I:C)-pretreated MSCs exhibit strengthened effects in decreasing kidney ischemia/reperfusion injury [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although serum-free incubation decreased the viability of ADSCs, flagellin-activated ADSCs retained 73% viability after 48 h. Previous studies have reported that LPS, a TLR5 ligand, could protect MSCs from serum deprivation by stabilizing cell membrane and activating ERK and PI3K/Akt signaling pathways ( 35 , 36 ). Given the similarities between TLR4 and TLR5, flagellin may exert its beneficial effects in similar ways ( 23 ). Therefore, ultrafiltration units with a 3-kDa molecular weight cutoff were used to concentrate CM, to retain the highest number of inflammatory regulators as possible.…”
Section: Discussionmentioning
confidence: 99%
“…TLR ligations can activate the immune defensive function of MSCs and alter their secretome profiles. For example, TLR4 ligands can activate the NF-κB pathway in MSCs and induce MSCs to release a variety of molecules, including IL-6 and vascular endothelial growth factor ( 23 ). Therefore, priming MSCs with TLR ligations may be a promising method for enhancing their therapeutic effects.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the article titled “Preconditioning of Rat Bone Marrow-Derived Mesenchymal Stromal Cells with Toll-Like Receptor Agonists” [ 1 ], there was an error in the production of Figure 2(b) which resulted in some colouration being lost. The publisher apologises for introducing this error, and the corrected figure is shown below and is listed as Figure 1 :…”
mentioning
confidence: 99%